Application of enamel matrix derivative in conjunction with non‐surgical therapy for treatment of moderate to severe periodontitis: A 12‐month, randomized prospective, multicenter study. Issue 5 (21st October 2020) - Schallhorn, Rachel A.; McClain, Pamela K.; Benhamou, Veronique; Doobrow, Jennifer H.; Grandin, H. Michelle; Kasaj, Adrian
Abstract: Background: Treatment of periodontitis aims to halt progressive bone and attachment loss and regenerate periodontal structures. In this study, the effect of using an enamel matrix derivative (EMD) as an adjunct to non‐surgical periodontal therapy (test) versus non‐surgical therapy alone (control) was evaluated. Methods: A prospective, split‐mouth, multicenter study evaluated scaling and root planing (SRP) with and without EMD in 51 patients presenting with moderate to severe periodontitis (PPD = 5 to 8 mm) in at least 2 pockets per contralateral quadrants within the same arch. The primary outcome variable was change in clinical attachment level (CAL) after 12 months. Secondary variables included probing pocket depth (PPD), bleeding on probing (BoP), gingival margin level, dentin hypersensitivity, and percent of pockets converted to sites no longer requiring surgical treatment. Results: CAL changed significantly ( P < 0.001) from baseline to 12 months for both treatment modalities (test = –2.2 ± 1.5 mm versus control = –2.1 ± 1.3 mm) and similarly for PPD; the difference between groups was not significant. A significant difference, favoring test conditions, was observed in percentage of both healthy PPDs (pockets < 5 mm) and converted pockets (sites no longer requiring surgical treatment); 79.8% of test versus 65.9% of control sites. BoP decreased significantly more ( P < 0.05) in test sites (BoP at 17.8% test versus 23.1% control). Conclusions: Both test and control treatments resulted in significant improvements in CAL and PPD. The adjunct use of EMD with SRP resulted in significantly greater improvements in overall periodontal health with less frequent BoP and a higher number of healthy PPDs.